PENDIDIKAN KARAKTER POSITIF DALAM PERIBAHASA BANJAR - Siti Akbari (Multilingual, 2015)
This study discusses about Banjar proverbs as an education media of positivecharacter in daily life with the aim to describe Banjar proverbs that showspositive character education and becomes a treasures for insight aboutproverb. The method used in this analysis is qualitative descriptive method.From the analysis it is found that positive character education is able form to asuperior human, that is (1) to be an Indonesian who has good morals, attitude,and character. (2) To achieve an intelligent and rational society. (3) In thefuture, Indonesian should become an innovative and progress people. (4)Strengthen the spirit of 'we can', that everyone should find solution in everydifficulties. (5) Indonesian should become the true patriots who love the nation,the state, and their homeland.